2009
DOI: 10.1303/aez.2009.543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fipronil on the reproduction, feeding, and relative fitness of brown planthopper, Nilaparvata lugens

Abstract: Applications of fipronil (1.25ϫ10Ϫ2 mg) and fipronil (7.50ϫ10 Ϫ3 mg) significantly stimulated the fecundity of Nilaparvata lugens compared with the control. The stimulating effect of fipronil on fecundity was dose-dependent. Fifteen and 30 days after treatment, the quantity of honeydew significantly increased in 1.25ϫ10Ϫ2 mg fipronil treatment. Fifteen days after treatment, the effect of fipronil on the quantity of honeydew was dose-dependent. The results revealed that the fipronil treatment group had developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Similar fitness costs have been reported in nitenpyram‐resistant N. lugens , which showed significantly prolonged development times of nymph stages, APOP and TPOP, but significantly decreased longevity, egg survival rate and fecundity . Deleterious effects on some life‐history traits, including the survival rate, adult emergence rate, copulation rate, fecundity and hatchability, have also been observed when N. lugens develop resistance to imidacloprid, fipronil and chlorpyrifos . Decrease in fitness owing to sulfoxaflor resistance development has also been found in a laboratory‐selected strain of M. persicae , which showed a relative fitness of 0.83, with low adult longevity, low oviposition days and low fecundity compared with a susceptible strain .…”
Section: Discussionsupporting
confidence: 67%
“…Similar fitness costs have been reported in nitenpyram‐resistant N. lugens , which showed significantly prolonged development times of nymph stages, APOP and TPOP, but significantly decreased longevity, egg survival rate and fecundity . Deleterious effects on some life‐history traits, including the survival rate, adult emergence rate, copulation rate, fecundity and hatchability, have also been observed when N. lugens develop resistance to imidacloprid, fipronil and chlorpyrifos . Decrease in fitness owing to sulfoxaflor resistance development has also been found in a laboratory‐selected strain of M. persicae , which showed a relative fitness of 0.83, with low adult longevity, low oviposition days and low fecundity compared with a susceptible strain .…”
Section: Discussionsupporting
confidence: 67%
“…Sogawa and Pathak (1970) reported a positive relationship between ingestion and honeydew excretion by Nilaparvata lugens Stål (Hemiptera: Delphacidae), and honeydew weights were usually measured to quantify the amount of feeding by planthopper. Thus, feeding rate of S. furcifera was assayed using the honeydew excretion method previously described by Ling et al (2009). After 2 h starvation, a single second nymph stage S. furcifera was placed into a paraÞlm sachet (2.0 by 3.5 cm) and the sachets were hung on the infected or noninfected rice stems (rice plants at tillering stage), which were Ϸ10 cm above the water surface.…”
Section: Methodsmentioning
confidence: 99%
“…Honeydew contaminated with these insecticides harmed the hoverfly Sphaerophoria rueppellii (Wiedemann) (Diptera: Syrphidae). Excretion of contaminated honeydew by resistant hemipteran species has yet to be demonstrated; nevertheless, one study showed that individuals of Nilaparvata lugens Stal (Homoptera: Delphacidae) that were resistant to fipronil excreted honeydew during the 30 days that the experiment lasted (Ling et al ., 2009 ). Even though this study did not measure the concentrations of fipronil in honeydew, it seems likely that honeydew would be contaminated with fipronil.…”
Section: How Can Systemic Insecticides Reach Honeydew?mentioning
confidence: 99%